Feasibility to estimate mean systemic filling pressure with inspiratory holds at the bedside - Wijnberge, Marije; Jansen, Jos R. C.; Pinsky, Michael R.; Klanderman, Robert B.; Terwindt, Lotte E.; Bosboom, Joachim J.; Lemmers, Nikki; Vlaar, Alexander P.; Veelo, Denise P.; Geerts, Bart F. (Frontiers in Physiology, 2022)
Background A decade ago, it became possible to derive mean systemic filling pressure (MSFP) at the bedside using the inspiratory holds maneuver. MSFP has the potential to help guide hemodynamic care but the estimation is not yet implemented in common clinical practice. In this study, we assessed the ability of MSFP, vascular compliance (Csys) and stressed volume (Vs) to track two fluid boluses. Second, we assessed the feasibility of implementation of MSFP in the intensive care unit (ICU). Methods This was a prospective cohort study in adult patients admitted to the ICU after cardiac surgery. MSFP was determined using 3-4 inspiratory holds with incremental pressures (maximum 35 cm H2O) to construct a venous return curve. Two fluid boluses were administered; 100 mL and 500 mL, enabling to calculate Vs and Csys. Patients were randomized to crystalloid or colloid fluid administration. Trained ICU consultants acted as study supervisors and protocol deviations were recorded. Results 20 patients completed the trial. MSFP was able to track the 500 mL bolus (p<0.001) and a difference in response between crystalloids and colloids was present for the 100 mL fluid bolus (p=0.019), and in a post-hoc analysis also for the 500 mL bolus (p=0.010). In 16 patients (80%), Vs and Csys could be determined. Vs was median 2029 ml (IQR 1605-3164) and Csys was median 73 ml mmHg-1 (IQR 56-133). Conclusions MSFP can be measured at the bedside and provides insights into the hemodynamic status of a patient that are currently missing. Clinical feasibility of Vs and Csys was judged ambiguous based on the lack of required hemodynamic stability. Future studies should address the clinical obstacles found in this study and less invasive alternatives to determine MSFP should be further explored.